Mental Health Effects of Same-Sex Marriage Legalization - Shuai Chen; Jan van Ours (Tinbergen Institute, 2021)
Sexual minorities have had worse than average mental health, which may have to do with actual or perceived discrimination. Same-sex marriage legalization (SSML) is a typical anti-discrimination policy removing marital restrictions for sexual minorities. We study how this legislation affected mental health of sexual minorities in the Netherlands. Conducting a difference-in-differences analysis, we compare changes in mental health following the legalization between sexual minorities and heterosexuals. We find that SSML improved mental health of both married and non-married sexual minorities, which implies that marriage is not the only channel. Examinations of alternative mechanisms combined with literature suggest that the legislation may also take effect by improving societal tolerance as well as stabilizing partnerships and enriching the choice basket of partnership forms for sexual minorities.
Keywords: I12; I18; J12; J15; K36; 330; Same-sex marriage; Mental health; Sexual minorities